Recruitment and selection methods in SMEs in Republic of North Macedonia - Miloshevik, Valerija; Piperkova, Irina; Davitkovska, Elena (Institute of Economics-Skopje, 2020)
Recruitment has become one of the most important human resource practices for firm’s performance. Leading firms in the world continuously develop proactive recruitment strategies that encompass various mechanisms and techniques to attract bigger applicant pool. Tight labor markets and fierce market competition impose greater challenges to SMEs. Hence, small and medium enterprises face additional challenges in recruiting adequate skills. A primary research was conducted among SMEs in the Republic of North Macedonia to examine their most practiced recruitment and selection methods. The findings reveal that SMEs apply a variety of traditional recruitment and selection methods, yet they need to develop more comprehensive recruitment strategy and seek additional alternative recruitment channels.
Keywords: recruitment, selection, SMEs, Republic of North Macedonia